Argentina : Assessment of Capital Market Mechanisms for Financing of SMEs - World Bank Group (World Bank, Washington, DC, 2017)
This document has the purpose of identifying and describing actions that could aid in facilitating the financing of Small and Medium Enterprises (SMEs) through instruments channeled via the capital markets. By way of precedent, it is worthwhile to mention the document ‘Argentina capital market assessment and development prospects’ of the World Bank (October 2016) where a diagnosis was performed (along with certain recommendations) of the Argentine capital markets in general and including sectoral aspects within which Small and Medium Enterprises (SMEs) and the capital market were analyzed. The structure of the document comprises the following sections: (a) characteristics of SME financing and the main obstacles they face; (b) analysis of proposals; (c) key players; (d) main conclusions; and (e) annexes including comparative country cases.